The signal intensity variation of multiple sclerosis (MS) lesions on magnetic resonance imaging (MRI) as a potential biomarker for patients’ disability: A feasibility study - Sedaghat, Sam; Jang, Hyungseok; Athertya, Jiyo S.; Groezinger, Martin; Corey-Bloom, Jody; Du, Jiang (Frontiers in Neuroscience, 2023)
Introduction: Although many lesion-based MRI biomarkers in multiple sclerosis (MS) patients were investigated, none of the previous studies dealt with the signal intensity variations (SIVs) of MS lesions. In this study, the SIVs of MS lesions on direct myelin imaging and standard clinical sequences as possible MRI biomarkers for disability in MS patients were assessed. Methods: 27 MS patients were included in this prospective study. IR-UTE, FLAIR, and MPRAGE sequences were employed on a 3T scanner. Regions of interest (ROIs) were manually drawn within the MS lesions, and the cerebrospinal fluid (CSF) and signal intensity ratios (SIR) were calculated from the derived values. Variations coefficients were determined from the standard deviations (Coeff 1) and the absolute differences (Coeff 2) of the SIRs. Disability grade was assessed by the expanded disability status scale (EDSS). Cortical/gray matter, subcortical, infratentorial, and spinal lesions were excluded. Results: The mean diameter of the lesions was 7.8±1.97 mm, while the mean EDSS score was 4.5±1.73. We found moderate correlations between the EDSS and Coeff 1 and 2 on IR-UTE and MPRAGE images. Accordingly, Pearson’s correlations on IR-UTE were R=0.51 (p=0.007) and R=0.49 (p=0.01) for Coeff 1 and 2, respectively. For MPRAGE, Pearson’s correlations were R=0.5 (p=0.008) and R=0.48 (p=0.012) for Coeff 1 and 2, respectively. For FLAIR, only poor correlations could be found. Conclusions: The SIVs of MS lesions on IR-UTE and MPRAGE images, assessed by Coeff 1 and 2, could be used as novel potential MRI biomarkers for patients’ disability.